2006
DOI: 10.1038/sj.ijo.0803226
|View full text |Cite
|
Sign up to set email alerts
|

A study of central fatness using waist-to-height ratios in UK children and adolescents over two decades supports the simple message – ‘keep your waist circumference to less than half your height’

Abstract: A study of central fatness using waist-to-height ratios in UK children and adolescents over two decades supports the simple message -'keep your waist circumference to less than half your height' Objective: To examine the influence of age and gender on the waist:height ratio (WHTR) in children and to compare changes over time in WHTR, a measure of central fatness in British children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
447
8
35

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 515 publications
(522 citation statements)
references
References 20 publications
(20 reference statements)
19
447
8
35
Order By: Relevance
“…Previous literature has found that the WHtR, rather than BMI and WC, was more strongly correlated with cardiovascular comorbidities and was better at predicting the metabolic syndrome in adults and cardiovascular health risks, such as high BP and high blood lipids, in adults and children (18,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) .…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has found that the WHtR, rather than BMI and WC, was more strongly correlated with cardiovascular comorbidities and was better at predicting the metabolic syndrome in adults and cardiovascular health risks, such as high BP and high blood lipids, in adults and children (18,(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37) .…”
Section: Discussionmentioning
confidence: 99%
“…The WHtR cut-point of 0.5 has several advantages over the other measures and cut-points; it is easy to calculate, does not require sex-and age-specific centiles (which are often not readily available to clinicians) and as previously suggested, 2 it is a simple message, easily understood by clinicians and families, to 'keep your waist circumference to less than half your height'.…”
Section: Discussionmentioning
confidence: 99%
“…WHtR has been shown to more readily identify adolescents with adverse cardiovascular risk factors compared to waist circumference and body mass index (BMI) 3 and a WHtR cutpoint of 0.5 has been proposed as a simple means of indicating whether the amount of central adiposity is excessive and a health risk in children. 2 However, the validity of these cut-points has not been examined in relation to metabolic outcomes in adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35] The waist:height ratio also shows some promise as useful measure of size-adjusted central adiposity. [36][37][38] The addition of circumferential measures may help to address the major weakness of BMI: its inability to distinguish between elevated adiposity and elevated lean mass. From a public health perspective, the observation that BMI in children and adolescents A Must and SE Anderson from 1987 to B1997 waist circumferences of British children increased more than BMI 33 suggests that surveillance by BMI alone may obscure important changes in body composition 39 at the population level.…”
Section: Looking To the Futurementioning
confidence: 99%